PREEKLAMSIA BERAT PADA IBU HAMIL DI RSUD RADEN MATTAHER JAMBI - Diniyati Diniyati; Lia Artika Sari; Ayu Nurma Afriyanti (Poltekkes Kemenkes Jambi, 2021)
Background: The ages that are considered to be at risk at birth are under 20 years and over 35 years. Whereas between 20-35 years of age is a healthy reproductive age with minimal risk of childbirth, mothers who have a history of preeclampsia pregnancy will be at 8.81 times greater risk of getting pregnant again with preeclampsia compared to mothers who do not have a history of preeclampsia Method: This research is a quantitative study with a cross sectional design that aims to determine the factors associated with the incidence of severe preeclampsia in pregnant women in the Raden Mattaher General Hospital of the Province of 2018. The population in this study were all pregnant women who visited the Raden Mattaher Regional Hospital in Jambi Province in the year 2018 as many as 289 people. The sample technique with total sampling is 122 pregnant women who have severe preeclampsia. This research was conducted in Raden Mattaher General Hospital Jambi from 17 June to 4 July 2019. Data in this study used secondary data in the form of medical record data in Raden Mattaher General Hospital in 2018. The analysis used in this study was univariate and bivariate and analyzed by chi-square. Results: The results showed that there was a relationship between the age of pregnant women and preeclampsia with p-value 0.000, there was a correlation between the characteristics of maternal parity with preeclampsia with p-value 0.000 there was a relationship between gravida mothers with preeclampsia cases with p-value 0.004. Conclusion: There is a relationship between the age of pregnant women, maternal parity characteristics and gravida with preeclampsia.